'Coz football is what we all have': masculinities, practice, performance and effervescence in a gender‐sensitised weight‐loss and healthy living programme for men. Issue 5 (11th February 2016) - Bunn, Christopher; Wyke, Sally; Gray, Cindy M.; Maclean, Alice; Hunt, Kate
Abstract: In this paper we use a social practice approach to explore men's experience of Football Fans in Training (FFIT), a group‐based weight management programme for men that harnesses men's symbolic attachment to professional football clubs to engage them in lifestyle change. FFIT is delivered by community coaches in clubs' stadia and is gender‐sensitised in relation to context, content and style of delivery. Using a 'toolkit' of concepts from the work of Bourdieu, Goffman and Durkheim we analysed data from 13 focus group discussions with participants, and fieldwork notes from programme observations to investigate the appeal and success of FFIT, and how it worked to support change. Our analysis builds on our work on the importance of shared symbolic commitment to the football club and being with 'men like me' to understand how the interaction context facilitated 'effervescent' experiences. These experiences encouraged men to make changes to their diet and physical activity, talk about them, practice performing them and implement them in their lives. Thus a social practice approach illuminated the social processes through which lifestyle change was achieved, and we argue that it can deepen and enrich both intervention design and evaluation.